Effect of isolated compounds from Combretum trifoliatum on toxicity and detoxification enzymes in Nilaparvata lugens - Nutchaya Kumrungsee; Saksit Nobsathian; Worakawee Chumworathayee; Poonnanan Phankaen; Benjawan Dunkhunthod; Opender Koul; Chatwadee Saiyaitong; Vasakorn Bullangpoti (Scientific Reports)
Abstract The brown planthopper (BPH) Nilaparvata lugens (Stål) is a major insect pest of Oryza sativa that causes crop yield loss in tropical regions, including Thailand. In this study, the crude ethanolic extract of the leaves and branches of Combretum trifoliatum , its active isolated components, apigenin and camphor, and Finopril were tested for their ability to control the first to fifth instars of N. lugens. The C. trifoliatum crude extract and both allelochemicals showed insecticide potential (24 h-LC50 ~ 8.83–95.96 mg/L against each instar for crude extract), and their toxicity depended on the time of exposure. Camphor showed the higher efficacy (LD50 ~ 4.43 mg/L) and not different compared to Finopril. All plant compounds tested reduced carboxylesterase (CE) and glutathione-s-transferase (GST) activities. Camphor caused the greatest decreases in CE and GST activities after exposure, whereas apigenin induced a slight change in acetylcholinesterase activity. The results of the present study suggest that C. trifoliatum extract can be used as an insecticide to manage N. lugens populations.